Meeting in solidarity with the imprisoned anarchist couple Kyritses condemned to 9 and 6 years for alleges possesion of molotov cocktails. Series of 2 photos
Meeting in solidarity with the imprisoned anarchist couple Kyritses condemned to 9 and 6 years for alleges possesion of molotov cocktails. Series of 2 photos.